A pseudomolecule‐scale genome assembly of the liverwort Marchantia polymorpha. (13th December 2019) - Diop, Seydina I.; Subotic, Oliver; Giraldo‐Fonseca, Alejandro; Waller, Manuel; Kirbis, Alexander; Neubauer, Anna; Potente, Giacomo; Murray‐Watson, Rachel; Boskovic, Filip; Bont, Zoe; Hock, Zsofia; Payton, Adam C.; et al.
Summary: Marchantia polymorpha has recently become a prime model for cellular, evo‐devo, synthetic biological, and evolutionary investigations. We present a pseudomolecule‐scale assembly of the M. polymorpha genome, making comparative genome structure analysis and classical genetic mapping approaches feasible. We anchored 88% of the M. polymorpha draft genome to a high‐density linkage map resulting in eight pseudomolecules. We found that the overall genome structure of M. polymorpha is in some respects different from that of the model moss Physcomitrella patens . Specifically, genome collinearity between the two bryophyte genomes and vascular plants is limited, suggesting extensive rearrangements since divergence. Furthermore, recombination rates are greatest in the middle of the chromosome arms in M. polymorpha like in most vascular plant genomes, which is in contrast with P. patens where recombination rates are evenly distributed along the chromosomes. Nevertheless, some other properties of the genome are shared with P. patens . As in P. patens, DNA methylation in M. polymorpha is spread evenly along the chromosomes, which is in stark contrast with the angiosperm model Arabidopsis thaliana, where DNA methylation is strongly enriched at the centromeres. Nevertheless, DNA methylation and recombination rate are anticorrelated in all three species. Finally, M. polymorpha and P. patens centromeres are of similar structure and marked by high abundance of retroelements unlike in vascular plants. Taken together, the highly contiguous genome assembly we present opens unexplored avenues for M. polymorpha research by linking the physical and genetic maps, making novel genomic and genetic analyses, including map‐based cloning, feasible. Significance Statement: Marchantia polymorpha has recently become a prime model for cellular, evolutionary‐developmental, synthetic biological, and evolutionary investigations with highly fragmented genomic resources (genome draft published in 2017; nearly 3000 scaffolds). To this end, we generated a pseudomolecule‐scale genome assembly of M. polymorpha, which will help to advance plant science by making comparative genome structure analysis and classical genetic mapping approaches feasible.